2005
DOI: 10.1007/s00256-005-0920-0
|View full text |Cite
|
Sign up to set email alerts
|

Tophaceous gout in the cervical spine

Abstract: Gout is a common metabolic disorder typically affecting the distal joints of the appendicular skeleton. Involvement of the axial skeleton, particularly the facet joints and posterior column of the cervical spine, is rare. This case report highlights such a presentation in a 76-year old female who presented with cervical spine pain following a fall. Her radiological findings were suggestive of a destructive metastatic process. Histological diagnosis confirmed tophaceous gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…4,5 An analysis of the literature indicated that all segments of the spine could be involved with gout. [6][7][8][9] The lower lumbar spine is the most common region involved, particularly the L4-5 level. [10][11][12][13] Only 20 cases of tophus in the dorsal vertebrae have been described in the literature (see Table 1 6-20 ).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 An analysis of the literature indicated that all segments of the spine could be involved with gout. [6][7][8][9] The lower lumbar spine is the most common region involved, particularly the L4-5 level. [10][11][12][13] Only 20 cases of tophus in the dorsal vertebrae have been described in the literature (see Table 1 6-20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia often goes untreated for a long time, as in the case of our patient. The lesions can occur in any area of the cervical spine, but are most frequently seen in C4-7 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). If severe neurological symptoms are present, orthopedic surgery is usually performed; otherwise a course of drug treatment is prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Photomicrograph of another section had been stained by de Galantha's method for demonstration of monosodium urate crystals ( Figure 2). subcutaneous nodules, knee, acromioclavicular joint and axial skeleton [3][4][5][6][7][8][9][10][11][12][13][14]. A recent study suggested that the frequency of axial involvement may be as high as 14% in patients with clinical or crystal-proven gout [15].…”
Section: Case Reportmentioning
confidence: 99%